Identifying the Apparent Key Attributes in Determining extremely Satisfied Restaurant Patrons during the Current Pandemic - Ambuli, Dr.T.V.; Vijayalakshmi, Dr. P. (The journal of contemporary issues in business and government, 2021)
The goal of the study is to identify the perceived key quality attributes that significantly distinguish highly satisfied diners from non-highly satisfied diners. A sample of 113 restaurant diners were included in this empirical study, in which consumers’ perception on four factors: food, physical environment, service and corona precautions were measured using a validated scale. Independent t test and weighted average test were used to determine which quality attributes are critical in distinguishing highly satisfied diners from other diners. The findings facilitate restaurant management in better allocating their resources and making improvements to critical quality factors that influence customer satisfaction.